Miniature Crafts and Their Makers : Palm Weaving in a Mexican Town - Flechsig, Katrin (Book collections on Project MUSE., 2004)
"Flechsig places the crafts of Chigmecatitlan within the contexts of manufacturing, local history, religion, design and technique, and selling. She tells how innovation is introduced into the craft, such as through the modification of foreign designs in response to market demands. She also offers insights into capitalist penetration of folk traditions, the marketing of folk arts, and economic changes in modern Mexico."--Jacket.